Analysis of Liability (Ḍamān) Based on “Delictual Exchange” and its Impact on Lawsuits of Civil Responsibility - ??????, ????????; ?????, ???? (???????? ??????? ?????? ????)
There are two major viewpoints in jurisprudence concerning the analysis of the nature of delictual liability (ḍamān-i qahrī). One viewpoint analyzes liability based on mere damage and the other based on delictual exchange. What is meant by delictual exchange in regard to delictual liability is that the ownership of the wasted property is, by order of the judge, handed over to the perpetrator of the damage and the ownership of its substitute (badal) to the person who has incurred the loss. With this analysis, the delictual exchange of badal and mubaddal (substituted) is by the judge’s order, whose   approval has significant impacts in the field of civil responsibility. For instance, according to this disposition, the components left over from the wasted property and the due rights belong to the perpetrator of damage, or in some instances that the usurped property is utilized somewhere and is valueless due to separation, the person who has incurred a loss merely deserve demanding its substitute and cannot ask for the very usurped property besides the damage. Similarly, acceptance of delictual exchange can be resulted in presentation of a new theory concerning the nature of ḥaylūla (lit. break or separation) substitute under the title of exchange of the inaccessible property’s benefits and the substitute.